The role of interactive radio programming in advancing women’s empowerment and crop and dietary diversity: Mixed methods evidence from Malawi - Ragasa, Catherine; Mzungu, Diston; Kalagho, Kenan; Kazembe, Cynthia (International Food Policy Research Institute, 2020)
The study assesses the effect of interactive radio programming on women’s empowerment and agricultural development, employing nationally representative household panel data and qualitative interviews in Malawi. Four major findings can be highlighted. First, radio programming is the preferred source of agricultural and nutrition advice among many subpopulations: younger women and men used radio more than other sources for their agricultural information needs, while younger and older men used radio more than other sources for nutrition education. Second, results show a positive impact of radio programming on technology awareness but a limited impact on actual adoption of most agricultural practices being promoted, except crop residue incorporation. Third, results show positive impacts on dietary diversity and adoption of other nutrition practices among the rural population. Fourth, results show a strong association between access to interactive radio programming and women’s and men’s empowerment scores. The association is greater for women’s empowerment and younger men’s empowerment, the latter being the most disempowered group in the sample.